Quantitative pupil analysis in stimulated emission depletion microscopy using phase retrieval - Kromann, Emil; Juette, Manuel Friedrich (Optics letters, 2012)
The resolution attainable with stimulated emission depletion (STED) microscopy greatly depends on the quality of the STED laser focus. So far, visual inspection of a measured STED focus has been the only convenient means of gauging the source of aberrations. Here we describe a method, requiring no instrument modifications, for obtaining an equivalent to the complex pupil function at the back aperture of the objective and show that it provides quantitative information about aberration sources (including aberrations induced by the objective or sample). We show the accuracy of this field representation to be sufficient for reconstructing the STED focus in three dimensions and determining corrective steps.